2018
DOI: 10.1038/s41598-018-30133-1
|View full text |Cite
|
Sign up to set email alerts
|

Growth of, and diffusion in, olivine in ultra-fast ascending basalt magmas from Shiveluch volcano

Abstract: Complex core-rim zoning of Mg-Fe-Ni-Ca-Cr-Al-P in high-Mg olivine crystals from a tuff ring of Shiveluch volcano, Kamchatka, enables reconstruction of the entire olivine crystallization history from mantle conditions to eruption. Bell-shaped Fo86–92 and Ni profiles in crystal cores were formed by diffusion after mixing with evolved magma. Diffusion proceeded to the centres of crystals and completely equilibrated Fo and Ni in some crystals. Diffusion times extracted from Fo and Ni core profiles range from 100 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 56 publications
0
32
1
1
Order By: Relevance
“…A striking feature of the olivine crystals from the earliest tephra is their alternating and sharp variation of high and low Fo and Ni concentrations, which are correlated with the alternating P variations. These observations are not common in olivine crystals from monogenetic volcanoes 16 , 47 49 , but have been reported in eruptions from Kamchatka (Shiveluch volcano 14 ) and kimberlites of South Africa (Benfontein 26 ). Such sharp and large compositional variations of Fo, Ni, and P imply significant changes of the intensive variables, which when combined with the skeletal shapes of the crystals and the inferred short timescales, indicate that the olivine grew fast in a very dynamic environment, with significant changes in temperature and f O 2 , possibly as the magma was moving towards the surface.…”
Section: Resultsmentioning
confidence: 65%
See 1 more Smart Citation
“…A striking feature of the olivine crystals from the earliest tephra is their alternating and sharp variation of high and low Fo and Ni concentrations, which are correlated with the alternating P variations. These observations are not common in olivine crystals from monogenetic volcanoes 16 , 47 49 , but have been reported in eruptions from Kamchatka (Shiveluch volcano 14 ) and kimberlites of South Africa (Benfontein 26 ). Such sharp and large compositional variations of Fo, Ni, and P imply significant changes of the intensive variables, which when combined with the skeletal shapes of the crystals and the inferred short timescales, indicate that the olivine grew fast in a very dynamic environment, with significant changes in temperature and f O 2 , possibly as the magma was moving towards the surface.…”
Section: Resultsmentioning
confidence: 65%
“…Mineral textural and compositional features, such as rare Mg-Fe oscillatory zoning in olivine 14 , have generally been attributed to open system magmatic processes in the mantle 14 or at shallower depths 15 . Petrological and geochemical studies of monogenetic eruptions have shown that many magmas contain multiple populations of crystals that imply the existence of shallow and probably ephemeral magma reservoirs 14 , 16 19 , rather than simply direct transport from the mantle to the surface. Interactions and mixing between multiple magma batches prior to eruption is common, and may be one of the conditions for the magmas to reach the surface and thus the eruption to occur 20 .…”
Section: Introductionmentioning
confidence: 99%
“…3; 4e, f). P has a low diffusivity in olivine (Watson et al 2015) and will, therefore, preserve compositional growth zonation, while Mg-Fe, Mn, and Ni will tend to become equilibrated by diffusion (Milman- Barris et al 2008;Bouvet de Maissonneuve et al 2016;Gordeychik et al 2018). Several correlated peaks The lines start at the crystal cores and trace olivine compositions towards forsteritic mantles and then back towards the low-Fo rim.…”
Section: Composition Of Olivine Phenocrysts In East Eifel Basanitesmentioning
confidence: 99%
“…Therefore, this is solid evidence that the Mg-Fe gradients are the result of a diffusion-dominated process. Further, the relationship between Fo-content and NiO also allows distinguishing growth from diffusion due to the different diffusion of Mg-Fe and Ni (Gordeychik et al 2018). For normally zoned olivine, growth results in a steep convex trend from core to mantle in a NiO-Fo diagram ( Fig.…”
Section: Our Approach To Diffusion Modelingmentioning
confidence: 99%
See 1 more Smart Citation